THE IMPLEMENTATION OF PQ4R LEARNING METHOD TO IMPROVE THE STUDENTS’ READING COMPREHENSION OF THE 4 th GRADE AT SD MUHAMMADIYAH 6 PEKANBARU - Faraditha Dwi Ramayani; Lazim N; Zufriady (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this research is to improve students reading comprehension at the fourth grade of SD Muhammadiyah 6 Pekanbaru. The type of this research was classroom action research, which was in two cycles. The result showed that there was an increasing students’ reading comprehension ability in each cycle. The average grade score of students reading comprehension before implementing PQ4R learning method was 68. After the implementation of PQ4R method at cycle I, the average grade score increased to 76 with a large increased of 12%. In the second cycle, the score increased to 84 with a large increased of 23%. In the cycle I, the teacher’s activities in the first meeting were 62.5% in moderate criteria. Then, in the second meeting, the percentage increased to 70.8% in moderate criteria. Then in the cycle II, the teacher’ activities in the first meeting the percentage became 83.3% in high criteria and in the second meeting increased to 87.5% in very high criteria. In the cycle I, the students’ activites in the first meeting were 58.3% in low criteria. In the second meeting, it increased to 66.7% in moderate criteria. In the cycle II, the students’ activities in the first meeting had the percentage becoming 79.2% in high criteria and then increased to 83.3% in high criteria on the second category. The result of the research proves that the application of PQ4R method can improve students’ reading comprehension ability.